2021
DOI: 10.3390/genes12030425
|View full text |Cite
|
Sign up to set email alerts
|

Wheat Varietal Response to Tilletia controversa J. G. Kühn Using qRT-PCR and Laser Confocal Microscopy

Abstract: Tilletia controversa J. G. Kühn is a causal organism of dwarf bunt in wheat. Understanding the interaction of wheat and T. controversa is of practical and scientific importance for disease control. In this study, the relative expression of TaLHY and TaPR-4 and TaPR-5 genes was higher in a resistant (Yinong 18) and moderately resistant (Pin 9928) cultivars rather than susceptible (Dongxuan 3) cultivar at 72 h post inoculation (hpi) with T. controversa. Similarly, the expression of defensin, TaPR-2 and TaPR-10 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…Pathogenesis-related genes have key roles in the plant defense system against fungal pathogen infection ( Sels et al, 2008 ). Based on the literature, thaumatin, chitinase, peroxidase, glucanase, and PR-10 enhance resistance to T. controversa and F. pseudograminearum in wheat ( Desmond et al, 2008 ; Muhae-Ud-Din et al, 2020b ; Chen et al, 2021 ), and Ustilaginoidea virens in rice ( Han et al, 2015 ). Consistent with our findings, PR genes in wheat have been induced by T. controversa ( Ren et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pathogenesis-related genes have key roles in the plant defense system against fungal pathogen infection ( Sels et al, 2008 ). Based on the literature, thaumatin, chitinase, peroxidase, glucanase, and PR-10 enhance resistance to T. controversa and F. pseudograminearum in wheat ( Desmond et al, 2008 ; Muhae-Ud-Din et al, 2020b ; Chen et al, 2021 ), and Ustilaginoidea virens in rice ( Han et al, 2015 ). Consistent with our findings, PR genes in wheat have been induced by T. controversa ( Ren et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Based on comparative transcriptomic analysis, many mycoblastosis (MYB) transcription factors and defense-related genes ( Thilmony et al, 2006 ; Mukherjee et al, 2010 ; Proietti et al, 2013 ) were found to be involved in defense mechanisms and in primary and secondary resistance-associated signal transduction paths of plants. For example, defense-related genes were found to be significantly upregulated in wheat after T. controversa inoculation ( Ren et al, 2020 ), phytohormone-related genes were upregulated in potato after Ralstonia solanacearum ( Zuluaga et al, 2015 ), and MYB transcription factor families were upregulated in wheat after T. controversa ( Chen et al, 2021 ) and R. cerealis infections ( Shan et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…After recording the fluorescence spectral data of the fresh leaves, the samples of the healthy, symptomatic and asymptomatic leaves were assessed using laser scanning confocal Confocal scanning laser microscopy is a powerful tool that provides structural information in time and space both at the tissue and atomic levels [106] and has numerous applications in the plant science including the studies on plant-pathogen interactions, pathogen infection strategies, fungal structures, plant defense responses and plant disease diagnostics. Confocal microscopy has been reported to be successfully used in wheat, for example (1) early detection of leaf rust [107] and blast and Fusarium head blight [108], (2) to study wheat-Tilletia controversa (dwarf bunt) interaction [109], and (3) to examine tissue localization and spatial distribution of protein and phenolic constituents [110][111][112].…”
Section: Fluorescence Confocal Microscopymentioning
confidence: 99%
“…Yield losses caused by these diseases can reach 70–80% or total loss of wheat production in a severe attack [ 4 , 5 ]. DBW and CBW cause leaf flecking, extreme dwarfing, increased tillering and reduced quality and quantity of kernels by releasing bunt ball teliospores [ 6 , 7 , 8 ] and are mostly noted in cold wheat growing regions of world [ 9 ]. Both diseases have been reported to be as high in China, USA and other wheat growing areas [ 2 , 10 ].…”
Section: Introductionmentioning
confidence: 99%